Structural characterization of a polysaccharide from Qi-Gui herb pair and its anti-tumor activity in colon cancer cells - Liu, Wen-Juan; Ma, Ye-Zi; Li, Jia-Xin; Fan, Bei-Sheng; Li, Xiao-Qiang; Cao, Wei; Tang, Yu-Ping (Frontiers in Pharmacology, 2025)
Astragalus membranaceus (Fisch.) Bunge and Angelica sinensis (Oliv.) Diels forms a classic herb pair (Qi-Gui her pair) in Chinese medicine, which was commonly used for treating menstrual anemia and microvascular ischemic diseases. While polysaccharides are known to be key bioactive components of the Qi-Gui herb pair, their structural characteristics and pharmacological activities remain underexplored. In this research, a homogeneous polysaccharide with a molecular weight of 18.1 kDa was isolated, and its structure was analyzed via high pressure size exclusion chromatography, high performance liquid chromatography, gas chromatography mass spectrometry, and nuclear magnetic resonance spectroscopy. The structural analysis revealed that AAPS-1a was composed of α-T-Glcp (5.9%), β-1,3-Galp (3.9%), α-1,4-Manp (3.6%), α-1,4-Galp (2.1%), α-1,4-Glcp (2.8%), and α-1,6-Glcp (81.7%). Furthermore, NMR analysis revealed that AAPS-1a consists of a repeat unit: α-T-Glcp-(1→4)-α-Galp-(1→4)-α-Manp-(1→4)-α-Glcp-(1→[6)-α-Glcp-(1]n→3)-β-Galp-(1→. In vitro studies showed that AAPS-1a could significantly inhibit the proliferation of HCT116 cells, and induces G1 arrest and G2/M arrest, as well as apoptosis of HCT116 cells. This study presents the inaugural report establishing a connection between the structural characteristics of Qi-Gui herbal polysaccharides and their anti-colon cancer activity, demonstrating that AAPS-1a holds promise as a therapeutic agent for the treatment of colon cancer.